The «principle of responsibility» in Adolphe Gesché’s theology - García Mourelo, Santiago (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2021)
Adolphe Gesché indicated the «principle of responsibility» as one of those that should guide theological work. Be responsible for faith and reason, for God and man. In the present study we expose his understanding and the particular development of this task in his work Dieu pour penser, attending to the double theological-fundamental movement —ad intra and ad extra— with which he used to articulate his writings.